Longer duration of symptoms at the time of presentation is not associated with worse survival in primary bone sarcoma. (May 2018) - Lawrenz, J. M.; Styron, J. F.; Parry, M.; Grimer, R. J.; Mesko, N. W.
Abstract : Aims: The primary aim of this study was to determine the effect of the duration of symptoms (DOS) prior to diagnosis on the overall survival in patients with a primary bone sarcoma. Patients and Methods: In a retrospective analysis of a sarcoma database at a single institution between 1990 and 2014, we identified 1446 patients with non-metastatic and 346 with metastatic bone sarcoma. Low-grade types of tumour were excluded. Our data included the demographics of the patients, the characteristics of the tumour, and the survival outcome of patients. Cox proportional hazards analysis and Kaplan–Meier survival analysis were performed, and the survivorship of the non-metastatic and metastatic cohorts were compared. Results: In the non-metastatic cohort, a longer DOS was associated with a slightly more favourable survival (hazard ratio (HR) 0.996, 95% confidence interval (CI) 0.994 to 0.998, p < 0.001). In all types of tumour, there was no difference in survival between patients with a DOS of greater than four months and those with a DOS of less than four months (p = 0.566). There was no correlation between the year of diagnosis and survival (p = 0.741). A diagnosis of chondrosarcoma (HR 0.636, 95% CI 0.474 to 0.854, p = 0.003) had the strongest positive effect on survival, while location in the axial skeleton (HR 1.76, 95% CI 1.36 to 2.29, p < 0.001) had the strongest negative effect on survival. Larger size of tumour (HR 1.05, 95% CI 1.03 to 1.06, p < 0.001) and increased age of the patient (HR 1.02, 95% CI 1.01 to 1.03, p < 0.001) had a slightly negative effect on survival. Metastatic and non-metastatic cohorts had similar median DOS (16 weeks, p = 0.277), although the median survival (15.5 months vs 41 months) and rates of survival at one year (69% vs 89%) and five years (20% vs 59%) were significantly shorter in the metastatic cohort. Conclusion: A longer DOS prior to diagnosis is not associated with a poorer overall survival in patients with a primary bone sarcoma. Location in the axial skeleton remains the strongest predictor of a worse prognosis. This may be helpful in counselling patients referred for evaluation on a delayed basis. Cite this article: Bone Joint J 2018;100-B:652–61.